Alcohol poisoning as a medical problem at the clinical ward of children’s emergency medicine - Skotnicka-Klonowicz, Grażyna; Grochocińska, Patrycja; Kuziemska, Anna (Polish Journal of Public Health, 2011)
Aim. The aim of the study was the analysis of patients who, in the last year, were treated for alcohol poisoning at The Clinical Ward for Children’s Emergency Medicine in the University Clinical Hospital No. 4 in Lodz, with special regard to injuries suffered while under the influence of alcohol. Material and methods. The analysis was based on medical history of the children treated for alcohol poisoning at the Emergency Ward from June 2008 to May 2009 . Results. There were 24,026 children admitted to the Emergency Ward during the examined time period, 64 (0.27%) of whom for alcohol intoxication. The number of boys (37) was slightly higher than that of girls (27). The age of the children was from 8 to 17 years, with almost a half of them between the age of 14-16 (31 children). The level of alcohol in the exhaled air ranged from 0.5 to 4.4 per mill. A similar amount of alcohol was diagnosed in the serum. In 49 of the children, the general condition was qualified as the moderately serious or serious. The consciousness level was below 14 points, at the Glasgow scale, for 26 of the children (approximately 40%). Injuries suffered under the influence of alcohol were observed in18 out of 64 children (28%). The symptoms of the general contusion were noted in 9 of the cases, while 6 children had head injuries (including one child with the temple bone fracture) and 3 children had self inflicted incised wounds of the forearm. These children not only did require a laboratory diagnosis, but also radiography of the skull, computed tomography of the head, radiography of the osteo-skeletal system. Forty out of 64 children required hospital treatment (35 in The Clinical Ward of Emergency Medicine, three in the Pediatric Clinics and two in the Surgical Clinic). Only three of the children with the forearm wounds required surgical treatment and the remaining children were given conservative treatment (body warming, liquid therapy, painkillers). The time of the hospitalization did not exceed 8 hours at the Emergency Ward and 4 days in other hospital wards. Conclusions. The alcohol consumption phenomenon becomes more frequent for girls and includes groups of younger and younger children. Alcohol consumption by children and teenagers can be linked to injuries, generating costs connected with necessary diagnosis. Preventive actions should be directed at children from the first levels of primary school.